Ketosis After Cardiopulmonary Bypass in Children Is Associated With an Inadequate Balance Between Oxygen Transport and Consumption*. Issue 9 (September 2016) - Klee, Philippe; Arni, Delphine; Saudan, Sonja; Schwitzgebel, Valérie M.; Sharma, Ruchika; Karam, Oliver; Rimensberger, Peter C.
Abstract : Objectives: Hyperglycemia after cardiac surgery and cardiopulmonary bypass in children has been associated with worse outcome; however, causality has never been proven. Furthermore, the benefit of tight glycemic control is inconsistent. The purpose of this study was to describe the metabolic constellation of children before, during, and after cardiopulmonary bypass, in order to identify a subset of patients that might benefit from insulin treatment. Design: Prospective observational study, in which insulin treatment was initiated when postoperative blood glucose levels were more than 12 mmol/L (216 mg/dL). Setting: Tertiary PICU. Patients: Ninety-six patients 6 months to 16 years old undergoing cardiac surgery with cardiopulmonary bypass. Interventions: None. Measurements and Main Results: Metabolic tests were performed before anesthesia, at the end of cardiopulmonary bypass, at PICU admission, and 4 and 12 hours after PICU admission, as well as 4 hours after initiation of insulin treatment. Ketosis was present in 17.9% patients at the end of cardiopulmonary bypass and in 31.2% at PICU admission. Young age was an independent risk factor for this condition. Ketosis at PICU admission was an independent risk factor for an increased difference between arterial and venous oxygen saturation. Four hours after admission ( p = 0.05). Insulin corrected ketosis within 4 hours. Conclusions: In this study, we found a high prevalence of ketosis at PICU admission, especially in young children. This was independently associated with an imbalance between oxygen transport and consumption and was corrected by insulin. These results set the basis for future randomized controlled trials, to test whether this subgroup of patients might benefit from increased glucose intake and insulin during surgery to avoid ketosis, as improving oxygen transport and consumption might improve patient outcome. Abstract : Supplemental Digital Content is available in the text.